KESANTUNAN BERBAHASA SISWA KELAS XI IPA-1 SMA NEGERI 1 AMANDRAYA - Faulu, Fauluzaro Buulolo (Universitas Nias Raya, 2024)
The background to the problem in this research is that there are still students' language impoliteness in the learning process, such as criticizing directly using harsh words, deliberately accusing the partner, deliberately cornering the speech partner and so on. This research aims to describe students' language politeness related to the maxim of wisdom, maxim of generosity, maxim of respect, maxim of consensus, maxim of sympathy and maxim of humility in class XI IPA-1 SMA Negeri 1 Amandraya for the 2023/2024 academic year. descriptive approach. This research data was analyzed in three stages, namely data reduction, verification and conclusion drawing. The results of this study show that the cause of impoliteness in this study is a violation of the maxim of generosity/humility maxim, namely the language of students can reprimand with diction that is less than subtle, defend against wrong actions, highlight oneself mockingly, and speak inappropriately to the situation while derivatives of the maxim Respect is an honest but gentle reprimand, honest praise, rejection with apologies, orders with a questioning tone, rejection with a questioning tone and providing sincere support, while the maxim of wisdom is a maxim that requires participants in a conversation to increase other people's benefits or reduce other people's losses. Suggestions for future researchers, the results of this research can be used as material for further research on the principles of politeness in Indonesian.